Enhancing Indian onion (Allium Cepa L. var. aggregatum) extraction by microwave hydrodiffusion and gravity (MHG) method: Parametric study and optimization using FCCD design - Yeni Variyana; Murni Fitria; Raka Selaksa Charisma Muchammad; Mahfud Mahfud (Results in Engineering)
The aim of this study is to extract essential oil from Indian onion bulbs (Allium Cepa L. var. aggregatum) using the microwave hydrodiffusion-gravity (MHG) method. The operating parameters considered include drying pre-treatment, material size (1-3 cm), microwave power (300-600 W), and extraction time (15-75 min). Optimal extraction conditions were identified through a two-stage process: initially screening data using a full factorial design, followed by process optimization using a face-centred central composite design (FCCD). The oil yield increased with extraction time up to a certain point, after which it plateaued, indicating no further yield improvements. The size of the material had an impact on how well microwave energy transferred; smaller particles provided larger surface areas, which improved extraction efficiency. Furthermore, the reduction in moisture content due to drying directly affected essential oil production, leading to higher yields. Sudden temperature increases could negatively impact oil quality, making temperature control during extraction critical. The microwave power level also played a significant role in the extraction process. The highest oil yield, 2.78%, was obtained with an extraction time of 75 min, a microwave power of 600 W, and a material size of 1 cm. Additionally, the extracted onion oil contained cyclohexanol, 5-methyl-2-(1-methylethenyl), and Z-citral.